2002
DOI: 10.1073/pnas.202199999
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone in utero and at birth dictates how stressful experience will affect learning in adulthood

Abstract: Exposure to an acute stressful event can enhance learning in male rats, whereas exposure to the same event dramatically impairs performance in females. Here we tested whether the presence of sex hormones during early development organizes these opposite effects of stress on learning in males vs. females. In the first experiment, males were castrated at birth whereas females were injected with testosterone. Rats were trained as adults on the hippocampal-dependent learning task of trace eyeblink conditioning. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 47 publications
8
67
2
1
Order By: Relevance
“…Therefore, we were surprised that learned helplessness behavior did not emerge in females that were masculinized at birth. In a previous study, masculinization of the female brain reversed the effects of uncontrollable stress on classical conditioning (Shors and Miesegeas, 2002). Instead of reducing classical eyeblink conditioning, exposure to the stressful event facilitated learning in females; they responded like intact males do.…”
Section: Sex Differences In Helplessnessmentioning
confidence: 67%
See 3 more Smart Citations
“…Therefore, we were surprised that learned helplessness behavior did not emerge in females that were masculinized at birth. In a previous study, masculinization of the female brain reversed the effects of uncontrollable stress on classical conditioning (Shors and Miesegeas, 2002). Instead of reducing classical eyeblink conditioning, exposure to the stressful event facilitated learning in females; they responded like intact males do.…”
Section: Sex Differences In Helplessnessmentioning
confidence: 67%
“…Females from different litters were injected with 0.02 ml of sesame oil alone (n ¼ 14). This treatment has been used frequently to study the organizational effects of androgens on the brain and has been shown effective for masculinizing the female brain and many aspects of behavior (Barraclough and Gorski, 1961;Beatty and Beatty, 1970;Shors and Miesegeas, 2002).…”
Section: General Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In rats, exposure to an acute stressful event can facilitate learning in males, but impairs performance in female rats. 311,312 Furthermore, exposure to an elevated plusmaze, a rodent anxiety test, leads to decreased 5-HTergic activity in the dorsal raphe nuclei in female rats, but to decreased 5-HTergic activity in the medial raphe nuclei in males. 101 There is also data to indicate that male rats may adapt better to stress than females.…”
Section: Biopsychological Interactionsmentioning
confidence: 99%